(3GddeYGJ GdHQbjI aj GdfcJ GdJGQjNjIs - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3hHYO, agPG JYdjb SejJg GddeYGJ GdHQbjI aj GdfcJ GdJGQjNjI, hgj (B: (3GdfcJI GdChdi s
(3BNQgG (B:s
(3aj eMQe SfI SJ hYTQjf hKeGfeGjI LGA GdfGFH JfHc GdYdGFj NdYI hfbT Pdc aj MLQ aj LGeY Hf jfLc GfJgi s
(3GfXQ HQbe (B429 (3JGQjNs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B360 ; (3agQS OGQ GdcJH GdeUQjI (B- (3GdLRA (B8 - (3U (B216 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs